ANALYSIS OF STUDENT'S ABILITY IN COMPLETING OPERATIONS OF SUMMARY AND REDUCTION OF INTEGER NUMBERS - Aam Amaliyah; Hasanah Dwi Wahyuni; Shinta Anjani Nura; Nurul Sahidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2022)
This study aims to describe the abilities and difficulties experienced by students in solving arithmetic operations on addition and subtraction of integers in SDIT Bunayya class. The data was collected by using test, interview, observation, and documentation methods. From the interview data, it shows that in solving problems students do not understand the concept of addition and subtraction of integers, the factor causing the difficulties experienced by students in solving problems is the lack of willingness to learn from within students. Students are often lazy to learn mathematics, do not want to listen to the teacher's explanation when the lesson is in progress, students do not concentrate fully during teaching and learning activities, students are afraid to ask the teacher if they do not understand the material. The material being taught, students always assume that mathematics is very difficult, students are less careful when working on problems. The results showed that the learning activities facilitated by the teacher were included in the good category. The teacher presents the lesson in an interesting way so that the learning process is not boring. The discussion method is used during the learning process to encourage students to ask questions and discuss so that students can share ideas. Students have difficulty solving problems between positive integers and negative integers in the form of stories. Students have difficulty because students do not understand the concept of integers contextually. This can be overcome by using learning media and contextual emphasis on learning concepts and observing student development using the results of the evaluation at the end of the class.